The New Romanian Civil Code versus the Old Romanian Civil Code – Introductory Issues concerning the Principle of the Contract Relativity Effects – The Contract - FIRICĂ, Manuel Cristian (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The article approaches, by comparative analysis between the old Civil Code and the new Romanian Civil Code, the institution of contract and highlights the regulatory or nuance differences, faces the concept in the new Civil Code with its intellectual sources of European and North American origin, showing how much the new regulation owes to the contemporary legal postmodernism.
Keywords: the old Romanian Civil Code; the new Romanian Civil Code, contract; obligation; will agreement; legal relation